Feasibility of an interactive voice response system for monitoring depressive symptoms in a lower-middle income Latin American country. Issue 1 (December 2016) - Janevic, Mary; Aruquipa Yujra, Amparo; Marinec, Nicolle; Aguilar, Juvenal; Aikens, James; Tarrazona, Rosa; Piette, John
Abstract Background Innovative, scalable solutions are needed to address the vast unmet need for mental health care in low- and middle-income countries (LMICs). Methods We conducted a feasibility study of a 14-week automated telephonic interactive voice response (IVR) depression self-care service among Bolivian primary care patients with at least moderately severe depressive symptoms. We analyzed IVR call completion rates, the reliability and validity of IVR-collected data, and participant satisfaction. Results Of the 32 participants, the majority were women (78 % or 25/32) and non-indigenous (75 % or 24/32). Participants had moderate depressive symptoms at baseline (PHQ-8 score mean 13.3, SD = 3.5) and reported good or fair general health status (88 % or 28/32). Fifty-four percent of weekly IVR calls (approximately 7 out of 13 active call-weeks) were completed. Neither PHQ-8 scores nor IVR call completion differed significantly by ethnicity, education, self-reported depression diagnosis, self-reported overall health, number of chronic conditions, or health literacy. The reliability for IVR-collected PHQ-8 scores was good (Cronbach's alpha = 0.83). Virtually every participant (97 %) was "mostly" or "very" satisfied with the program. Many described the program as beneficial for their mood and self-care, albeit limited by some technological difficulties and the lack of human interaction. Conclusion Findings suggest that IVR could feasibly be used to provide monitoring and self-care education to depressed patients in Bolivia. An expanded stepped-care service offering contact with lay health workers for more depressed individuals and expanded mHealth content may foster greater patient engagement and enhance its therapeutic value while remaining cost-effective. Trial registration ISRCTN ISRCTN 18403214. Registered 14 September 2016. Retrospectively registered